O teleatendimento nas atividades de ensino de terapia ocupacional em disfunção física do adulto durante a pandemia de COVID-19: percepções dos alunos de um projeto de extensão - Guimarães, Ludmila Boaventura; Martim, Heloisa (Universidade Federal de São Carlos, 2022)
The outbreak of COVID-19 caused by the new coronavirus (SARS-CoV-2) has led to the confirmation of numerous cases and deaths in a short time worldwide. In March 2020, the World Health Organization (WHO) declared the new coronavirus a pandemic and from there, an effort by countries began to try to contain the spread of the virus. Of the measures taken, social isolation was the most effective, so far, being adopted both in Brazil and in other countries. Through social isolation, there was a change in people's behavior and habits, when they had to study and work at home by digital means. Federal Universities, in view of the scenario caused by the COVID-19 pandemic, established the suspension of face-to-face classes, as well as extension projects. In this way, teaching activities underwent changes in remote formats, as well as community service through extension and research projects. The objective of this study was to understand the perceptions of students from an Occupational Therapy undergraduate course at a Federal University in Telehealth in a University Extension Project. Based on this pandemic scenario and the adjustments for telehealth, the expected results in this research sought to understand what was the impact of this form of service for the formation of the student, what were the difficulties faced by them and to map their implications within the formation of undergraduates in the Occupational Therapy Course. The results that were found after data analysis were the following categories and thematic units respectively: Changes in Learning Processes (Challenges and development of new skills, Adaptation to remote care, Changes in student routine and Development of clinical reasoning); Differences in Health Care (Flexibility of strategies, Participation and bonding, Physical and social distancing, Understanding of everyday life and Use of technologies); Call center: how do I understand this strategy? (Continuity of Care), Social Isolation and Difficulties in the Teaching Activity (Use of technologies and digital tools, Bonding, Routine and Search for knowledge); Teaching Strategies (Learning Development); Guidance Material, (Contributions in the learning process, Use of Materials Produced); and, finally, Strategies and Difficulties in Telehealth (Strategies and Difficulties, Adequate Space, Technologies and Digital Tools, and Distance). Teaching and care underwent changes in their processes that generated great potential despite the challenges faced. Dealing with internet access problems, inadequate work and study space, new ways of evaluating and studying were just a part of what was built, but everything is opposed to the exchanges generated, the development of learning and the pro-activity of the students, as well as as the continuity of care provided to users with the flexibility of intervention strategies.
The telehealth in occupational therapy teaching activities in adult physical dysfunction during the COVID-19 pandemic: students' perceptions of an extension project
Keywords: Occupational Therapy; Teaching Activities; Pandemic; Telehealth; COVID-19; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL